Fatores que influenciam o balanço comercial de produtos fitossanitáros no Brasil - Gaban, Felipe Borghi (Universidade Federal de São Carlos, 2024)
Brazil is the second-largest consumer of agricultural pesticides in the world, only behind the United States. It is considered one of the major powers in the agricultural sector, with extensive areas dedicated to farming. There's an increasing need to enhance production yield while preventing losses due to field pests. This justifies Brazil's position as one of the largest importers of inputs, heavily reliant on the external market, particularly countries like China, India, and the United States. Therefore, the objective of this work is to analyze the importance of the agrochemical sector in the agribusiness supply chain using export and import data extracted from the COMEX system during key global supply crisis moments. It aims to identify the impacts in terms of price and imported volume. Additionally, it seeks to delve into concepts such as raw materials, technical products, formulated products, global value chains, and production models. This study also aims to contextualize the international and Brazilian production sector to comprehend the current process within the value chain.
Factors that influence the trade balance of phytosanitary products in Brazil
Keywords: Importação de defensivos agrícolas; Cadeia produtiva global; Agronegócio; Importation of agricultural pesticides; Global production chain; Agribusiness; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA